2017
DOI: 10.1136/bmjopen-2017-016291
|View full text |Cite|
|
Sign up to set email alerts
|

The relationship between school type and academic performance at medical school: a national, multi-cohort study

Abstract: ObjectivesDifferential attainment in school examinations is one of the barriers to increasing student diversity in medicine. However, studies on the predictive validity of prior academic achievement and educational performance at medical school are contradictory, possibly due to single-site studies or studies which focus only on early years’ performance. To address these gaps, we examined the relationship between sociodemographic factors, including school type and average educational performance throughout med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 41 publications
(24 reference statements)
1
38
0
Order By: Relevance
“…Kumwenda et al reported students from state schools achieve higher EPM scores than those attending independent schools, when entering medical school with similar grades [23]. This provides an interesting perspective on how well different school types prepare students for studying medicine but, as the authors of the study acknowledge, the findings need to be interpreted within the whole context of the individual's educational circumstances: attending a state school does not always demonstrate educational and social disadvantage.…”
Section: Introductionmentioning
confidence: 90%
“…Kumwenda et al reported students from state schools achieve higher EPM scores than those attending independent schools, when entering medical school with similar grades [23]. This provides an interesting perspective on how well different school types prepare students for studying medicine but, as the authors of the study acknowledge, the findings need to be interpreted within the whole context of the individual's educational circumstances: attending a state school does not always demonstrate educational and social disadvantage.…”
Section: Introductionmentioning
confidence: 90%
“…They also need more ongoing support than other pupils, particularly as they may find it harder to form social identities with their medical student peers (Brown & Garlick, 2006;Leathwood & O'Connell, 2003). Recent evidence however shows that students from state-funded schools outperform their peers who attended independent schools (Kumwenda et al, 2017). The same finding may therefore also be true of WP candidates.…”
Section: During Medical Schoolmentioning
confidence: 51%
“…Interestingly, these variables are related: independent schooling has been shown to be associated with lower EPM scores. 29,30 However, our parallel study of applications to GP training, 28 while also finding lower EPM scores to be associated with a greater likelihood of application, found independent schooling to be associated with a lower likelihood. Thus, while both specialties suffer recruitment shortages, the underlying reasons for this may be different.…”
Section: Discussionmentioning
confidence: 79%